Embracing virtual outpatient clinics in the era of COVID-19. (17th May 2021) - Lee, George; Clough, Oliver T.; Hayter, Edward; Morris, James; Ashdown, Thomas; Hardman, John; Anakwe, Raymond
Abstract : The response to the COVID-19 pandemic has raised the profile and level of interest in the use, acceptability, safety, and effectiveness of virtual outpatient consultations and telemedicine. These models of care are not new but a number of challenges have so far hindered widespread take-up and endorsement of these ways of working. With the response to the COVID-19 pandemic, remote and virtual working and consultation have become the default. This paper explores our experience of and learning from virtual and remote consultation and questions how this experience can be retained and developed for the future. Cite this article: Bone Jt Open  2021;2(5):301–304.